O processo de aprendizagem nos projetos tradicionais e ágeis - Gomes, Luciana Viel (2023)
Learning is reproduced through human practices, and within the project context it is no different. Dialogue, conversations and narratives between project participants are some of the mechanisms to cultivate learning. Strategically, the ability to learn has been considered an important factor and source of competitive advantage and success in organizations. There is a growing interest in the learning process in the organizational context, fueled by the belief that learning is essential for consolidation in competitive and dynamic environments. The result of this interest is a broad literature on the various dimensions of organizational learning and the learning organization. Therefore, the objective of the study was to evaluate the learning processes in traditional and agile projects in the perception of those involved in the project. To achieve the proposed objective, qualitative research was carried out with semi-structured interviews with professionals from agile and traditional projects. In the results, a framework was formulated with the learning processes in traditional and agile projects. The suggested framework serves as a guide for organizations to shape and refine their organizational learning methods in projects. This is based on four fundamental learning processes, called the 4Is: Intuition, Interpretation, Integration and Institutionalization. Each process is customized to reflect the requirements and practices peculiar to traditional, agile and hybrid methods in project management in organizations.